2013
DOI: 10.1007/s11103-013-0071-y
|View full text |Cite
|
Sign up to set email alerts
|

Tomato FRUITFULL homologues act in fruit ripening via forming MADS-box transcription factor complexes with RIN

Abstract: The tomato MADS-box transcription factor RIN acts as a master regulator of fruit ripening. Here, we identified MADS-box proteins that interact with RIN; we also provide evidence that these proteins act in the regulation of fruit ripening. We conducted a yeast two-hybrid screen of a cDNA library from ripening fruit, for genes encoding proteins that bind to RIN. The screen identified two MADS-box genes, FUL1 and FUL2 (previously called TDR4 and SlMBP7), both of which have high sequence similarity to Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 47 publications
6
89
0
Order By: Relevance
“…Our previous study found that FUL1 and FUL2 are plausible candidates for components of the ripening regulator complex. 20) In this study, we demonstrated that the suppression of FUL1 and FUL2 inhibited ripening, at least partially through ethylene-dependent pathways. These results are consistent with the hypothesis that the FUL homologs and RIN compose a complex that regulates ripening.…”
Section: Mads-box Tf Complexes Regulating Tomato Fruit Ripeningmentioning
confidence: 56%
See 4 more Smart Citations
“…Our previous study found that FUL1 and FUL2 are plausible candidates for components of the ripening regulator complex. 20) In this study, we demonstrated that the suppression of FUL1 and FUL2 inhibited ripening, at least partially through ethylene-dependent pathways. These results are consistent with the hypothesis that the FUL homologs and RIN compose a complex that regulates ripening.…”
Section: Mads-box Tf Complexes Regulating Tomato Fruit Ripeningmentioning
confidence: 56%
“…1) and the results of our previous study, 20) we hypothesized that FUL1 and FUL2 act redundantly in the regulation of fruit ripening. Therefore, we decided to suppress FUL1 and FUL2 simultaneously, and constructed an RNAi vector using a FUL2 fragment that shows 78% identity to the corresponding sequence of FUL1.…”
Section: Suppression Of Ful1 and Ful2 Inhibited Tomato Fruit Ripeningmentioning
confidence: 68%
See 3 more Smart Citations